2012
DOI: 10.1016/j.jrp.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Personality and substance use in midlife: Conscientiousness as a moderator and the effects of trait change

Abstract: Personality traits predict substance use in adolescence, but less is known about prospective substance use in middle age and beyond. Moreover, there is growing interest in how personality change and the multiplicative effects among personality traits relate to substance use. Participants included approximately 4,000 adults aged 25–74 who participated in two waves of the Midlife in the U.S. (MIDUS) study. Higher levels of neuroticism, extraversion, openness, and lower levels of conscientiousness and agreeablene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
181
8
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(214 citation statements)
references
References 52 publications
16
181
8
9
Order By: Relevance
“…However, whereas a previous meta-analysis with 4,730 participants found an association between low agreeableness and current smoking, this association was not found in the current study (12). In addition, contrary to prior longitudinal evidence (13)(14)(15)(16), neuroticism and openness to experience were not associated with smoking initiation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, whereas a previous meta-analysis with 4,730 participants found an association between low agreeableness and current smoking, this association was not found in the current study (12). In addition, contrary to prior longitudinal evidence (13)(14)(15)(16), neuroticism and openness to experience were not associated with smoking initiation.…”
Section: Discussioncontrasting
confidence: 99%
“…In prospective studies, high neuroticism has been shown to be associated with smoking initiation in some (13)(14)(15), but not in all studies (16). Low conscientiousness has been shown to be associated with smoking initiation (13,16), while the evidence of the association between high openness to experience and smoking initiation is mixed with both positive and null findings (13,16). Results from two small-scale smoking cessation programs suggests that low neuroticism and low openness to experience may be associated with higher odds of smoking cessation (17,18), and that higher conscientiousness might predict abstinence from smoking (17).…”
mentioning
confidence: 99%
“…This association occurs largely because neuroticism predicts engagement in unhealthy behaviors, including smoking and drinking (Turiano et al, 2012), and greater physiological stress reactivity (Lahey, 2009). Individuals high in neuroticism are also more Personality and Health Response 6 likely to use unhealthy behaviors, such as smoking and drinking, as a method to cope with stress (Malouff et al, 2007;Turiano et al, 2012).…”
mentioning
confidence: 99%
“…Some have suggested that neuroticism is healthy when paired with high conscientiousness, a trait that allows individuals to deal productively with stress (Gartland, O'Connor & Lawton, 2012). When paired with high conscientiousness, high neuroticism has been found to predict lower levels of smoking (Turiano et al, 2012) and better physical health (Roberts, Smith, Jackson & Edmonds, 2009;Turiano et al, 2013). Thus, while conscientiousness has consistent associations with positive health -and thus is expected to predict adaptive responses to health news -the links between neuroticism and health are more complex, and so it is unclear whether neuroticism will predict responses or in what direction.…”
mentioning
confidence: 99%
“…On the other hand, these personality traits have an impact on all mental and physical aspects of an individual in a way that many components, including health, [10,11] creativity, [12] drug use, [13] and life satisfaction [14,15] could be predicted by these characteristics.…”
Section: Original Articlementioning
confidence: 99%